The mitochondrial Ca(2+) uptake regulator, MICU1, is involved in cold stress‐induced ferroptosis - Nakamura, Toshitaka (EMBO Rep, 2021)
Ferroptosis has recently attracted much interest because of its relevance to human diseases such as cancer and ischemia‐reperfusion injury. We have reported that prolonged severe cold stress induces lipid peroxidation‐dependent ferroptosis, but the upstream mechanism remains unknown. Here, using genome‐wide CRISPR screening, we found that a mitochondrial Ca(2+) uptake regulator, mitochondrial calcium uptake 1 (MICU1), is required for generating lipid peroxide and subsequent ferroptosis under cold stress. Furthermore, the gatekeeping activity of MICU1 through mitochondrial calcium uniporter (MCU) is suggested to be indispensable for cold stress‐induced ferroptosis. MICU1 is required for mitochondrial Ca(2+) increase, hyperpolarization of the mitochondrial membrane potential (MMP), and subsequent lipid peroxidation under cold stress. Collectively, these findings suggest that the MICU1‐dependent mitochondrial Ca(2+) homeostasis‐MMP hyperpolarization axis is involved in cold stress‐induced lipid peroxidation and ferroptosis.